The influence of patient-related factors on the frequency and duration of psycho-oncological sessions in a university cancer center - Madl, Martina; Lieb, Marietta; Schieber, Katharina; Erim, Yesim (Journal of Psychosocial Oncology, 2021)
Objective The present study aimed at identifying factors that are associated with the frequency and duration of psycho-oncological sessions. Design In a retrospective single-center study, data of all patients who made use of the psycho-oncological service (POS) at the University Hospital Erlangen from April 2017 - March 2018 were registered. Sample Over the course of one year, N = 1601 patients made use of the POS. Methods In the hospital's digital documentation system, relevant data such as frequency of sessions, duration of sessions, gender, age, family status, preexisting mental disorder, prior psychotherapy, cancer entity (type of cancer) and treatment modality were recorded. Socio-demographic and clinical parameters were analyzed to predict frequency and duration of the psycho-oncology sessions. Findings Regression analyses revealed that among POS users, women, younger patients, patients with a longer hospital stay and those with a preexisting mental disorder attended significantly more sessions than other patients (p < .001). Patients with skin cancer had significantly fewer POS sessions than those with a hematological diagnosis. Also, patients who had undergone surgery had significantly fewer sessions than patients with pharmacological treatment. Younger age and a longer hospital stay significantly predicted longer sessions (p < .001). In the regression model, patients with brain tumors and lung cancer had significantly longer sessions than patients with skin cancer. Implications With the identification of specific risk groups that require more and longer sessions, we can provide the basis for more patient-tailored intervention approaches and better scheduling according to the patients' needs. However, our results also suggest that the frequency and duration of POS sessions also depend on illness- and treatment-related criteria, e.g. the length of the hospital stay.
CRIS-Team WoS Importer:2021-12-10